Resisting the Abuse of Jesus’s Jewishness: Lessons from Modern and Medieval Palestine - Azar, Michael G. (Studies in Christian-Jewish Relations, 2026)
This article examines the modern political and theological use of Jesus’s Jewishness within Jewish-Christian relations, arguing that its frequent deployment in support of nationalist agendas constitutes an abuse rather than a recovery of Jesus’s historical and theological particularity. Focusing on Western Jewish-Christian discourse from the mid‑twentieth century to the present, the study shows how appeals to Christianity’s alleged forgetfulness of Jesus’s Jewish identity have repeatedly been mobilized to legitimate Zionist interests while marginalizing or silencing Palestinian Christians. Such moves, the article contends, are often sustained by reductive portrayals of Christian history and by an uncritical application of the language of “appropriation.” To complicate these assumptions, the article turns to the theology and sociopolitical context of John of Damascus, an eighth‑century Palestinian Christian thinker who neither denied nor instrumentalized Jesus’s Jewishness. John’s exegetical account of Christ as one who “made his own the face of the Jews” offers a premodern example of affirming Jesus’s Jewish identity without deploying it for political domination or excluding other particularities of place and community. Drawing these modern and medieval contexts into dialogue, the article argues for a more historically attentive and ethically responsible approach to Jesus’s Jewishness—one that resists its nationalist instrumentalizations, supports Jewish-Christian reconciliation, and takes seriously the lived realities of Christianity in Palestine.